Impact of crossover second toe on the postoperative outcome of distal chevron osteotomy for moderate to severe hallux valgus. Issue 8 (December 2020) - Park, Young Hwan; Kim, Woon; Kim, Jae Young; Choi, Gi Won; Kim, Hak Jun
Highlights: In the study period, 18% of patients with moderate to severe hallux valgus showed a crossover second toe that needed surgical treatment. In the short-term, patients with moderate to severe hallux valgus combined with crossover second toe showed slower functional recovery than patients without crossover second toe. In the long-term, overall outcomes were similar for moderate to severe hallux valgus, regardless of whether or not it was combined with a crossover second toe. Abstract: Background: Crossover second toe is often presented in moderate to severe hallux valgus. However, its clinical impact on the postoperative outcome of hallux valgus is still unknown. Methods: Thirty-five patients who had moderate to severe hallux valgus with crossover second toe were matched with 35 controls who did not have crossover second toe, according to preoperative hallux valgus angle and first-second intermetatarsal angle. Radiological parameters, Foot Function Index (FFI), and Visual Analog Scale (VAS) were assessed as postoperative outcomes at 3, 6, and 12 months after surgery. Results: At 3 months, the FFI in the crossover second toe group was lower than in the control group (p = 0.001), while other outcomes were similar. On the other hand, there were no significant differences between the groups at 6 and 12 months, in terms of radiological parameters, FFI, and VAS. Conclusions: Patients who had moderate to severe hallux valgus with crossover second toe were at risk for slow functional recovery after surgical treatment in the short term, but, in the long-term, there was no difference in overall postoperative outcomes in patients with and without crossover second toe. Level of Evidence: Level III, retrospective comparative study.